RECYCLING OF ASPHALT PAVEMENT AGGREGATES AND WASTE PLASTIC BOTTLES IN ADDITION TO HOT-MIX ASPHALT PRODUCTION: ADEQUATE RECYCLING RATE - Birega, Tibebu; Geremew, Anteneh (Journal of Civil Engineering, Science and Technology, 2024)
This study focused on the recycling of asphalt pavement aggregates and waste plastic bottles (WPB) in addition to hot-mix asphalt (HMA) production. To achieve this objective, non-probable sampling methods were used to gather samples from the study locations. Crushed stone aggregate (CSA), bitumen, mineral filler, reclaimed asphalt pavement aggregate (RAPA), and WPB were the ingredients employed based on the requirements in the standard specification for asphalt concrete production. Initially, the Marshall Stability Test was then carried out using CSA with 6% and bitumen levels of 4.0, 4.5, 5.0, 5.5, and 6% by weight of the total mix to ascertain what the bitumen content should be with RAPA with replacement rates of 10, 20, and 30% and that of WPB with 2, 6, 8, 10, 12, and 14%. In the Marshall Stability Test, which consisted of three trials of 195 samples and 60 mix designs, 45 were for the control mix and 150 for the replacement proportion. In the Marshall Stability Test, the ideal value for CSA was 5.1%; for RAPA, 5.1%; and for WPB, 7.7, 5.5, 5.4, 5.0, 5.5, and 5.4% optimum bituminous content (OBC). 20% RAPA and 10% WPB by weight of OBC in the stability-modified asphalt mix satisfies Ethiopian Road Authority (ERA) and American Society for Testing and Material (ASTM) specifications for all qualities tested. Finally, for improved asphalt mix performance, a combined 70% CSA, 20% RAPA, and 10% WPB should be used in asphalt mixes at 5.0% OBC. These experimental Marshal Stability Test findings satisfy the necessary specifications of ERA and ASTM for all tests used in HMA production. Thus, this proportion is strongly advised.